Will Older Persons and Their Clinicians Use a Shared Decision-making Instrument? - Naik, Aanand D (Blackwell Science Inc, 2005)
OBJECTIVE: To examine experiences of older persons and their clinicians with shared decision making (SDM) and their willingness to use an SDM instrument. DESIGN: Qualitative focus group study. PARTICIPANTS: Four focus groups of 41 older persons and 2 focus groups of 11 clinicians, purposively sampled to encompass a range of sociodemographic and clinical characteristics. APPROACH AND MAIN RESULTS: Audiotaped responses were transcribed, coded independently, and analyzed by 3 reviewers using the constant comparative method. Patient participants described using informal facilitators of shared decision making and supported use of an SDM instrument to keep “the doctor and patient on the same page.” They envisioned the instrument as “part of the medical record” that could be “referenced at home.” Clinician participants described the instrument as a “motivational and educational tool” that could “customize care for individual patients.” Some clinician and patient participants expressed reluctance given time constraints and unfamiliarity with the process of setting participatory clinical goals. CONCLUSIONS: Participants indicated that they would use a shared decision-making instrument in their clinical encounters and attributed multiple functions to the instrument, especially as a tool to facilitate agreement with treatment goals and plans.